Sistem Kendali Otomatis Pengendalian serta Pemantauan Level Volume dan Suhu Kerja Digester Berbasis Internet of Things - Ahmad Mahfud; Singgih Wirapratama (JURNAL CITRA WIDYA EDUKASI, 2021)
This research discusses the application of an automatic control system for controlling and monitoring the volume level and working temperature of the Digester based on the Internet of Things. The digester machine is a machine that still uses a manual system for controlling and monitoring the volume level and working temperature. This research was conducted through the literature study stage, observing the monitoring system and controlling the volume level and working temperature of the digester machine directly in the field, designing the control system, testing and analyzing as a whole on how the control system works on a miniature digester machine. The result showed that: 1) the control system for controlling and monitoring the volume level and working temperature of the digester can work stably and continuously; 2) the measurement result by the sensor have an error rate of 1.747% for the controller sensor and 1.520% for the monitoring sensor; 3) data on the result of monitoring the volume level and working temperature have been integrated with the internet through the Ubidots IoT platform; 4) data can be monitored remotely using a smartphone via the Ubidots Explorer application; and 5) the design and construction of the equipment greatly influences the work of the control system, because the machine (digester), as an application medium, must be able to support the work of the control system later.